Inisiasi Kalus Embriogenik Stroberi (Fragaria sp.) dengan Pemberian IBA (Indolebutyricacid) dan BAP (Benzylaminopurine) - DEWI, AGUNG WIDYA ANTASARI; DARMAWATI, IDA AYU PUTRI; SEMARAJAYA, COKORDA GEDE ALIT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
Initiation Of Embryogenic Callus Strawberries (Fragaria sp.) By Giving IBA (Indolebutyric Acid) and BAP (Benzylaminopurine) Micropropagation or multiplication method by vegetative that could produce seedling in the high number and in a short time, had the same character as its mains, with a progress that not depends on the weather. This research intend to find the effect of grow regulator IBA (Indolebutyric Acid) and BAP (Benzyl aminopurine) and to find the best combination on producing callus strawberry. This research done in Unit Pelaksanaan Teknis (UPT) kultur jaringan Program Study Agroekoteknologi, Faculty of Agriculture, Udayana University. The materials use by the base of strawberry leaf. Growth regulators IBA and BAP could grown a callus. Usage 0,5 ppm IBA + 0,5 ppm BAP is the most effective in deflexion. Relative fast in deflexion (2,6 days). Usage 1 ppm IBA + 1 ppm BAP is the most effective in expansion (6,3 days) but in 30 days mandating its not grown any callus. It require toned to study the sterilisasion method to minimize the contamination and browning in explants strawberry leaf and a tool that in use to do research more to get the right concentration with IBA and BAP combination to get the callus.
Keywords: Initiation; Embriogenic; callus; Strawberry; IBA (Indolebutyric Acid); BAP (Benzyl aminopurine)